Hypoglycemia Event Rates: A Comparison Between Real-World Data and Randomized Controlled Trial Populations in Insulin-Treated Diabetes. Issue 1 (March 2016) - Elliott, Lisa; Fidler, Carrie; Ditchfield, Andrea; Stissing, Trine
Abstract Introduction Hypoglycemia is the most common adverse effect of diabetes therapy, particularly insulin treatment. Hypoglycemia is associated with considerable clinical and economic burden, and may be under-reported. The aim of this study was to com pare the frequency of hypoglycemic events reported in real-world settings with those reported in clinical trials. Methods We conducted a structured literature review in PubMed to identify hypoglycemic event rates in patients with type 1 diabetes mellitus (T1DM) and insulin-treated type 2 diabetes mellitus (T2DM) from real-world data (RWD) and randomized controlled trials (RCTs). The search was restricted to English language, full-text publications from 2010 onwards, reporting on treatment of T1DM or T2DM with basal only, basal-bolus, or premix insulin. Results The final dataset included 30 studies (11 RWD studies and 19 RCTs). Six studies (RWD, n  = 2; RCT, n  = 4) reported hypoglycemia event rates in people with T1DM. For all reported categories of hypoglycemia (severe, non-severe, and nocturnal), rates were consistently higher in RWD studies compared with RCTs. Twenty-five studies (RWD, n  = 10; RCT, n  = 15) reported hypoglycemia event rates in people with insulin-treated T2DM. For T2DM basal-oral therapy; the highest rates were observed in RWD studies, although there was an overlap with RCT rates. For basal-bolus therapy, there was considerable between-study variability but higher rates of severe and non-severe hypoglycemia were generally observed in RWD studies. For T2DM premix insulin, reported rates of hypoglycemia in RWD studies and RCTs were similar. Conclusion We found that higher rates of hypoglycemia are observed in real-world settings compared with clinical trial settings, although there is a large degree of overlap. Due to the inherent constraints of RCTs, they are likely to underestimate the burden of hypoglycemia in clinical practice. Further, high-quality RWD are needed to determine a more accurate incidence of hypoglycemia in clinical practice.